2022
DOI: 10.1111/btp.13081
|View full text |Cite
|
Sign up to set email alerts
|

Impoverished woody seedling assemblages and the regeneration of Caatinga dry forest in a human‐modified landscape

Abstract: Seedling recruitment, community assembly, and forest regeneration, while receiving substantial attention in tropical rain forests, have received little attention in tropical dry forests. Here, we examine the structure, composition, and diversity of woody seedling assemblages across 19 forest stands in a human‐modified landscape of Caatinga dry forest, assessing the role played by rainfall, aboveground biomass, and chronic anthropogenic disturbances (i.e., livestock grazing pressure and wood extraction) as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Moreover, a recent study has shown that LCA negatively impact regenerating plant assemblages (Knoechelmann et al, 2020). This finding highlights the role of LCA as an additional biotic driver of the low seedling density reported for humanmodified Caatinga dry forest (Vanderlei et al, 2022). However, the negative impacts of LCA on regeneration might be higher if we consider potential effects on other regeneration mechanisms such as the new seed input after disturbance.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, a recent study has shown that LCA negatively impact regenerating plant assemblages (Knoechelmann et al, 2020). This finding highlights the role of LCA as an additional biotic driver of the low seedling density reported for humanmodified Caatinga dry forest (Vanderlei et al, 2022). However, the negative impacts of LCA on regeneration might be higher if we consider potential effects on other regeneration mechanisms such as the new seed input after disturbance.…”
Section: Introductionmentioning
confidence: 71%
“…Accordingly, the ultimate impact of LCA on seed fate and plant recruitment in the Caatinga dry forest depends on the extension to which seeds dropped along the trails escape from density-dependent mortality and thus compensate for the role played by ant nests as seed sinks and/or a source of seedling mortality. In fact, a seed/seedling sink function of LCA nest, particularly in the plant recruitment season, might serve as a reasonable explanation for seedling rarity in our focal landscape (Vanderlei et al, 2022), but also for taxonomically distinct seedling assemblages in LCA-affected habitats (Bieber et al, 2011;Knoechelmann et al, 2020;Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Although almost all angiosperm woody plants have the ability to sprout studies have shown that the predominance of regrowth behavior is related to the level of vegetation disturbance, specifically with the vegetation structure of Brazilian Caatinga (Barros et al, 2021). Such an attribute is quite common in seasonally dry tropical forests (SDTFs) when compared to other tropical forests (Vanderlei et al, 2022). Despite these generalizations, regrowth ability varies according to the disturbance intensity, frequency and type, and number of tillers of C. pyramidale were only negatively influenced by HAI, while the number of tillers of C. blanchetianus was influenced by the density of human trails (TRAN) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of 50% of dry forests worldwide has drastically altered the infiltration capacity of their soils, as agricultural practices compact and seal soils with long-lasting negative effects on water availability ( Leite et al, 2018 ). The subsequent drought stress has aggravated seedling mortality and selected towards a set of resprouting species, leading to biotic homogenization in dry forests ( Barros et al, 2021 ; Vanderlei et al, 2022 ). The limited infiltrability of soils under disturbance not only reduces the local water availability, including ground-water recharge and soil water holding capacity ( Abdallah et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%